THE EFFECT OF PROFITABILITY, COMPANY SIZE, SALES GROWTH AND LEVERAGE ON FIRM VALUE - Santioso, Linda (Graduate Program of Universitas Tarumanagara, 2025)
The purpose of this study is to ascertain how firm value is impacted by factors such as leverage, sales growth, company size, and profitability in infrastructure sector companies that are listed on the Indonesia Stock Exchange (IDX) between 2019 and 2021. Purposive sampling was the method utilized in this study's sample selection process. After processing the data with the eviews 13 program, the study's findings offer empirical support for the following claims: leverage has a significant positive effect firm value; company size has no apparent negative impact on value; sales growth has no apparent negative impact on value; and profitability has a significant negative impact on value. The implication of this research is that the sample taken in 2019-2021 where in 2020-2021 there was an economic crisis impact from the co-19 pandemic, if the profitability obtained by a company is only momentary due to economic instability, it does not necessarily increase the value of the company. Company value will be good or increase if the profitability of a company is obtained continuously. Company size does not necessarily have good value for investors, the larger the size of a company will usually require a lot of funding for company operations which are usually obtained from debt. Debt will cause a burden for the company, meaning that if the debt is not managed properly, then instead of increasing the value for the company, it will even cause a burden or problem for the company. Sales growth is not always a benchmark for investors in making investments. If sales growth is not accompanied by increased profitability, it is very detrimental to the Company, meaning that the Company has exerted all its energy but the results are not optimal. Leverage, which is represented by the debt to equity ratio (DER), a high DER value often assumes that the company is sick. If the company can use debt for operations efficiently, so that the company is growing, it will affect the value of the company, so that investors assume that the company is able to manage debt and does not hesitate to invest.